The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/w12092439
|View full text |Cite
|
Sign up to set email alerts
|

Response of Clementine Mandarin to Water-Saving Strategies under Water Scarcity Conditions

Abstract: Water scarcity is the most constraining factor for crop production, especially in arid and semi-arid areas of Mediterranean countries such as Morocco. Within these conditions, different water-saving strategies using deficit irrigation (DI) were tested on two six-years old clementine varieties (‘Sidi Aissa’ and ‘Orogrande’). These DI strategies were applied during the second part of fruit growth and during fruit maturation and included: the control treatment (Cntl), in which the trees received 100% of crop evap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The different patterns of ET o under semi-arid climates reported in the literature (Er-Raki et al, 2009Jafari et al, 2021;Tabari et al, 2012) do not differ from the pattern of the experiment. However, ET a values fall in the conventional range of 700-1300 (mm/year), with an average of 1000 (mm/year) (El-Otmani et al, 2020). The same range of values (765, 820, and 786 mm/year) was reported for citrus orchards in the Haouz region (Er-Raki et al, 2009, 2012El Hari et al, 2010;Nassah et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The different patterns of ET o under semi-arid climates reported in the literature (Er-Raki et al, 2009Jafari et al, 2021;Tabari et al, 2012) do not differ from the pattern of the experiment. However, ET a values fall in the conventional range of 700-1300 (mm/year), with an average of 1000 (mm/year) (El-Otmani et al, 2020). The same range of values (765, 820, and 786 mm/year) was reported for citrus orchards in the Haouz region (Er-Raki et al, 2009, 2012El Hari et al, 2010;Nassah et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
“…The assessment of crop evapotranspiration was done following the FAO-56 approach. Overall, the meteorological conditions are not strange in a region characterized by a semi-arid climate, which is dry and hot in summer and relatively cold in winter (El-Otmani et al, 2020). The issue of water scarcity in the area has been made worse by climate change and agricultural development (Marieme et al, 2017), which is confirmed by the low values of the aridity index.…”
Section: Discussionmentioning
confidence: 96%
“…Water scarcity, aggravated by the effects of climate change, is predicted to worsen due to more severe and frequent drought events in warm temperate climate regions ( Ronco et al., 2017 ; Galindo et al., 2018 ; Pedrero et al., 2020 ). This will decrease land suitability for fruit crops in many regions, especially in arid and semi-arid areas where rainfall is becoming less intense and frequent ( Ronchail et al., 2014 ; Galindo et al., 2018 ; Araya-Osses et al., 2020 ; El-Otmani et al., 2020 ; Meza et al., 2023 ). Increasing annual mean temperature due to climate change also threatens the availability of freshwater.…”
Section: Discussionmentioning
confidence: 99%
“…Along with reductions in water availability, higher temperatures increase evapotranspiration and crop water demand(Rai et al, 2015;del Pozo et al, 2019;Arenas-Castro et al, 2020;Fraga et al, 2020). The aforementioned conditions may explain the strong focus on water-saving strategies, such as water deficit irrigation management, that we observed in our analysis.Deficit irrigation has historically been the main strategy used in olive trees and grapevine to manage fruit quality(Fernandes de Oliveira et al, 2013;Galindo et al, 2018;Araujo et al, 2019;Buesa et al, 2019;Kokkotos et al, 2020;Siakou et al, 2021;Ibba et al, 2023; Ferrara et al, 2024), and it is becoming a popular strategy in other crops, including mandarins(El-Otmani et al, 2020), pomegranates(Galindo et al, 2018;Adiba et al, 2022), apples(Panzacchi et al, 2012;Kendall et al, 2022), almonds(Gutierrez- Gordillo et al, 2020;Barreales et al, 2023), peaches(Ruiz-Sańchez et al, 2018), apricots (Ezzat et al, 2021, and pistachios(Marino et al, 2018). In brief, the idea is to reduce the amount of water provided to the crop during the growing season, improving marketable yield per unit of water and end-product quality, rather than achieving maximum yields(Ronco et al, 2017;Galindo et al, 2018;El-Otmani et al, 2020).…”
mentioning
confidence: 99%